A multi-objective approach for resilience-based system design optimisation of complex manufacturing systems - Latsou, Christina; Erkoyuncu, John Ahmet; Farsi, Maryam (Elsevier, 2021)
Disruptive events in complex manufacturing systems (CMS), characterised by labour-intensive processes and repetitive activities, render these systems vulnerable. In order to tackle this challenge, an approach for resilience-based system design optimisation is proposed. The approach: (i) introduces a dynamic multi-dimensional resilience metric; and (ii) formulates the resilience as a multi-objective optimisation problem to improve CMSs resilience by finding an optimal human resource allocation model, considering design factors including redundancy, resources capacity and roles. The case study, selected to test the validity of the presented approach, show improvement in resilience and efficiency, in terms of throughput, resources utilisation and restoration time.
Keywords: Resilience design; complex manufacturing systems; dynamic multi-dimensional resilience; multi-objective optimisation; resource planning